1957
DOI: 10.5703/1288284313518
|View full text |Cite
|
Sign up to set email alerts
|

Pumping of Highway and Airfield Pavements: Technical Paper

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…It is seen that the plasticity index decreases as phosphogypsum content increases for the three soils, which are mainly due to a reduction in liquid limit. Previous studies on lime and cement treatment have shown similar effects on consistency limits of the treated soils as seen in Figure 9 taken from reference [1] and [2], which shows the effect of lime treatment on consistency limits of 13 clay soils, the effect of Portland cement treatment on Consistency limits of A-7-6 soil taken from Illinois State. It could be seen from these two figures that the liquid limit decreases, the plastic limit increases, and the plasticity index sharply decreases.…”
Section: Atterberg Limitssupporting
confidence: 65%
See 3 more Smart Citations
“…It is seen that the plasticity index decreases as phosphogypsum content increases for the three soils, which are mainly due to a reduction in liquid limit. Previous studies on lime and cement treatment have shown similar effects on consistency limits of the treated soils as seen in Figure 9 taken from reference [1] and [2], which shows the effect of lime treatment on consistency limits of 13 clay soils, the effect of Portland cement treatment on Consistency limits of A-7-6 soil taken from Illinois State. It could be seen from these two figures that the liquid limit decreases, the plastic limit increases, and the plasticity index sharply decreases.…”
Section: Atterberg Limitssupporting
confidence: 65%
“…It has a major influence on the design and construction of roadway pavements. Many studies and researches proved that highways constructed over plastic soil suffered from a high degree of distresses on the pavement [1,2]. Expansive soil is widely spread in Jordan and also all over the world.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, thanks to the camera, the pumping 31 up level of fine particles was visualized during the test, showing that the migration of fine particles was 32 not only due to the interpenetration of ballast particles and sub-soil, but also the pore water pressure that 33 al. 2011) and the pavement context (Yoder 1957, Van 1985, Alobaidi and Hoare 1994, 1998a, 48 1998b, 1999, Zhang 2004, Yuan et al 2007. By contrast, the interlayer has been identified and 49 characterized only recently (Calon et al 2010, Trinh et al 2011, Trinh 2011, Trinh et al 2012 2013, Duong et al 2013).…”
mentioning
confidence: 99%